EMPOWERING FAMILY BUSINESS : A STUDY OF FINANCIAL CAPABILITY, EXPERIENCE, AND KNOWLEDGE - Azis Ameyra, Maharani Qhayla Dhyapitaloka; Wiryakusuma, I Gusti Bagus Yosia; Budi Martono, Sarah Oktania Purnomo (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This research aims to examine the effect of building financial capacity on family businesses in Indonesia. This research uses the PLS-SEM research method with survey data collected from 65 sample respondents who are owners or manage business of family businesses in Indonesia. The results of this research show that building good financial capacity in a business is an important thing to do and has a positive influence on the development of a family business. This research shows that experience in finance influences financial knowledge and influences financial capacity in a family business. Besides all of that, experience in the financial sector also influences a person's capacity to manage finance in a family business. Family businesses tend to have their own unique financial reports so that experience in managing finances will have a big impact on financial performance in the family business. This research has important implications for practitioners, researchers and academics because it is an interesting matter to discuss. These findings can be used to develop the level of experience and financial management capacity in a family business. For academics, this research will have an impact on increasing knowledge and views regarding financial management in a business.